2006
DOI: 10.1017/s1743921307000567
|View full text |Cite
|
Sign up to set email alerts
|

The destruction of 3He by Rayleigh-Taylor instability on the first giant branch

Abstract: Abstract. Low-mass stars, ∼ 1 − 2 solar masses, near the Main Sequence are efficient at producing 3 He, which they mix into the convective envelope on the giant branch and distribute into the Galaxy by way of envelope loss. This process is so efficient that it is difficult to reconcile the observed cosmic abundance of 3 He with the predictions of Big Bang nucleosynthesis. In this paper we find, by modeling a red giant with a fully three-dimensional hydrodynamic code and a full nucleosynthetic network, that mix… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Send offprint requests to: E. Carretta, eugenio.carretta@oabo.inaf.it ⋆ Based on observations collected at ESO telescopes under programmes 072.D-507 and 073.D-0211 to also come with differences in the main outcome of the H burning, the He content (Gratton et al 2009;Bragaglia et al in preparation;Prantzos and Charbonnel 2006;Ventura et al 2001). Apart from a few alterations presently well understood in term of an extra-mixing episode after the red giant branch (RGB) bump (Charbonnel 1994(Charbonnel , 1995Charbonnel and Zahn 2007;Eggleton et al 2007) the abundance variations are inherited by currently observed, long lived GC stars from a previous stellar component/generation: both spectroscopic (Gratton et al 2001;Ramirez and Cohen 2002;Carretta et al 2004;Piotto et al 2005) and photometric (e.g. Bedin et al 2004) observations convincingly showed that the observed pattern of chemical composition is present also among unevolved stars on the subgiant branch and the main sequence.…”
Section: Introductionmentioning
confidence: 99%
“…Send offprint requests to: E. Carretta, eugenio.carretta@oabo.inaf.it ⋆ Based on observations collected at ESO telescopes under programmes 072.D-507 and 073.D-0211 to also come with differences in the main outcome of the H burning, the He content (Gratton et al 2009;Bragaglia et al in preparation;Prantzos and Charbonnel 2006;Ventura et al 2001). Apart from a few alterations presently well understood in term of an extra-mixing episode after the red giant branch (RGB) bump (Charbonnel 1994(Charbonnel , 1995Charbonnel and Zahn 2007;Eggleton et al 2007) the abundance variations are inherited by currently observed, long lived GC stars from a previous stellar component/generation: both spectroscopic (Gratton et al 2001;Ramirez and Cohen 2002;Carretta et al 2004;Piotto et al 2005) and photometric (e.g. Bedin et al 2004) observations convincingly showed that the observed pattern of chemical composition is present also among unevolved stars on the subgiant branch and the main sequence.…”
Section: Introductionmentioning
confidence: 99%